Big data analytics management capability and firm performance: the mediating role of data-driven culture - Karaboga, Tugba; Zehir, Cemal; Tatoglu, Ekrem; Karaboga, H. Aykut; Bouguerra, Abderaouf (SPRINGER HEIDELBERG, 2023)
The effect of big data analytics on firm performance and the effects of intermediary variables on this relationship are not yet clearly understood. Drawing on the dynamic capability view (DCV), this study investigates the mediating effect of a data-driven culture on the relationship between big data analytics management capability and firm performance (i.e., operational and financial performance). Drawing on survey data from 432 big data experts across 132 firms operating in Turkey, our findings indicate that big data analytics management capability and a data-driven culture have significant positive effects on both the operational and financial performance of a firm. In addition, a data-driven culture significantly mediates the links between big data analytics management capability and the measures of both operational and financial performance. Hence, our findings offer a valuable guide for managers utilizing big data or making big data investments to increase firm performance.
Keywords: Big data analytics capability; Data-driven culture; Dynamic capability view; Operational performance; Financial performance; SUPPLY CHAIN MANAGEMENT; PARTIAL LEAST-SQUARES; RESOURCE-BASED VIEW; DYNAMIC CAPABILITIES; BUSINESS-PROCESS; PREDICTIVE ANALYTICS; INNOVATION; ADOPTION; IMPACT; PATH; Business & Economics